Polyethylene glycol-based RAFT agent cum ATRP macroinitiator initiated block copolymerization of methyl methacrylate (Indian Journal of Chemical Technology (IJCT), 2023)
PMMA-b-PEG-b-PMMA block copolymer has been synthesized by the activators regenerated by electron transfer atom transfer radical polymerization (ARGET-ATRP) of methyl methacrylate (MMA) using modified polyethylene glycol (PEG) as initiator. PEG is chemically modified by CS2 followed by an esterification to incorporate initiating sites for ATRP as well as for RAFT polymerization. The prepared macroinitiator has been characterized by FT-IR and NMR analyses for its structural validation. FT-IR and NMR analyses confirmed the successful synthesis of the macro initiator. This macro initiator has been used to prepare ABA type triblock copolymer with MMA via ARGET-ATRP. The polymerization reaction is carried out using cupric bromide (CuBr2) as catalyst in combination with N,N,N′,N″,N″-pentamethyl diethylenetriamine (PMDETA) as ligand in N, N dimethyl formamide (DMF) at 70°C. Ascorbic acid is used as reducing agent. The conversion of the monomer was calculated gravimetrically. The successful preparation of the block copolymer is confirmed by FT-IR, 1H NMR and 13C NMR analyses. The MALDI-TOF mass analysis of the block copolymers also confirm the presence of monomer MMA, dithionate and PEG parts in the block copolymer. The purified block copolymer is analyzed by TGA, and SEM analyses. TGA analysis shows that the prepared block copolymer has better (Tmax = 366°C) thermal stability than the PMMA (Tmax = 349°C) homopolymer.